Implementación de un aplicativo web para la gestión de rutas, inventarios y aportaciones en la "Cooperativa de transporte Intraprovincial Río San Pablo". - Toala Mendieta, Toni Aldair (2023)
This research presents the implementation of a web application for the management of routes, inventory, and contributions in the "Cooperativa de Transporte Intraprovincial Rio San Pablo". The main objective of this project is to improve the efficiency and effectiveness of the cooperative's management by automating manual processes, which will allow for better decision-making and greater profitability. The research was based on an analysis of the current situation of the cooperative and the identification of critical areas that need improvement. Specific objectives of the implementation were established, including the registration and management of system users, the implementation of an appropriate security layer, the management of unit inventory, the management of unit routes, the registration of contributions from cooperative members, and the automatic creation of cards. For the implementation of the proposed solution, a methodology based on web technology was used, with programming languages and tools such as PHP, MySQL, JavaScript, and CSS. Tests and validations were carried out on each of the implemented modules, which allowed for the verification of the proper functioning of the application. The obtained results demonstrate that the implementation of a web application is an effective solution for improving the management of the Cooperativa de Transporte Intraprovincial Rio San Pablo. The application allowed for greater process automation, better information management, and greater efficiency in decision-making.